The Relationship Between Physical Activity And Sleep Quality With Premenstrual Syndrome (PMS) In Female Students - Ayu Agustina Rindani; Nurlailis Saadah; Teta Puji Rahayu; Budi Joko Santosa (International Journal of Advanced Health Science and Technology, 2022)
Young women who have menstruation may experience premenstrual syndrome (PMS) which will affect their quality of life. Premenstrual syndrome experienced can be bad for adolescents if not treated early. Therefore, teenagers are expected to be able to manage themselves as well as possible to avoid these problems. The purpose of this study was to determine the relationship between physical activity and sleep quality with the incidence of Premenstrual Syndrome (PMS). This research is an observational analytical study that is cross-sectional. Sampling using the slovin sample size formula, the sample was taken with a simple random sampling technique with a sample size of at least 39. The independent variables are physical activity and sleep quality, while the dependent variables are the incidence of Premenstrual syndrome (PMS). Data collection used the International Physical Activity Questionnaire (IPAQ), Pittsburgh Sleep Quality Index (PSQI), and The Shortened Premenstrual Assessment From (SPAF). To analyze the relationship, a spearman rank test with a meaningfulness level or error limit is used, namely p≤0.05. The results showed that most female students had moderate physical activity as many as 33 female students. Then it can be known that most experienced moderate sleep quality as many as 17 female college students. The results of the Spearman test ranked the relationship between physical activity and Premenstrual Syndrome p value = 0.326 so that Ho was accepted and the relationship of sleep quality with Premenstrual Syndrome p value = 0.044, so Ho was rejected. Based on the description above, it can be concluded that there is no significant relationship between physical activity and premenstrual syndrome but there is a significant relationship between sleep quality and premenstrual syndrome in level 3 female students of the Diii Obstetrics Study Program, Magetan Campus. It is hoped that female students can increase their knowledge in managing themselves from an early age so that Premenstrual Syndrome (PMS) does not occur.